Analisis Hubungan Antara Ekspor dan Impor Terhadap Pertumbuhan Ekonimi Di Indonesia - ainur rohma; Linda Putri Setyawati; Lailatul Fitri; Nuha Fawaida Ashari; Bustanurrahman Hamdani; Putri Catur Ayu Lestari (CV. ITTC INDONESIA, 2025)
This research seeks to examine how exports and imports influence Indonesia’s economic growth from 2010 to 2024. The study employs the analic regresi to assess the short-run and long-run dynamics among the variables. The dataset used is obtained from the Central Bureau of Statistics (BPS) and the World Bank, covering figures on export and import activities.